Analisis Sistem Penghargaan dan Beban Kerja terhadap Kinerja Perawat Pelaksana Rumah Sakit pada Masa Pandemi COVID -19 - Ismar Agustin; Muliyadi Muliyadi; Mutia Nadra Maulida (Jurnal Keperawatan Silampari, 2022)
This study aims to determine whether rewards and workload affect the performance of nurses in inpatient services at a hospital in Palembang City. This research is included in the category of ex-post-facto study and is also causally associative. The results showed that most of the nurses had vocational education (D III Nursing) with 100 nurses (74.6%), female 116 (86.6%), married 112 (83.4%), and permanent employment status 40 ( 29.9%) followed by Honor/contract/non-permanent 39 (29.1%). The analysis results obtained a p-value of 0.048 for the nurse workload variable with nurse performance and a p-value of 0.035 <0.05 for the reward system and nurse performance. In conclusion, there is a significant relationship between the reward system and version, and there is a substantial relationship between workload and performance. Keywords: workload, performance, nurses, reward system